The Management of Strengthening the Mosque-Based Religious Character Education - Badrudin Badrudin (FITK UIN Walisongo, 2019)
This study aims to explore the management of strengthening the religious character education of mosque-based students in madrasas. Data collection techniques using observation, interviews, and study documentation. Data analysis used qualitative analysis at Madrasah Aliyah Negeri 2 Kota Bandung. The results showed that the management of mosque-based character strengthening students had fulfilled management principles and was able to instill student character through worship activities. The design of activities to strengthen mosque-based character education that has been carried out includes thaharah, Duha praying, adhan, iqamah, recitation of asma alhusna, tadarus al-Quran, lectures, midday prayers, remembrance, and prayers. This activity is effectively able to develop the character of obedience, responsibility, discipline, cleanliness, neatness, trustworthy, confident, caring, brave and polite.AbstrakPenelitian ini bertujuan untuk mengeksplorasi manajemen penguatan pendidikan karakter religius peserta didik berbasis Mesjid di madrasah. Teknik pengumpulan data menggunakan observasi, wawancara, dan studi dokumentasi. Analisis data menggunakan analisis kualitatif di Madrasah Aliyah Negeri 2 Kota Bandung. Hasil penelitian menunjukkan bahwa manajemen penguatan pendidikan karakter peserta didik berbasis masjid telah memenuhi prinsip manajemen dan mampu menanamkan karakter siswa melalui aktifitas ibadah. Desain aktivitas penguatan pendidikan karakter berbasis mesjid yang telah dilakukan meliputi thaharah, sholat Duha, adzan, iqamah, pembacaan asma alhusna, tadarus al-Quran, kuliah, sholat dzuhur , zikir, dan sholat. Kegiatan ini secara efektif mampu mengembangkan karakter kepatuhan, tanggung jawab, disiplin, kebersihan, kerapian, dapat dipercaya, percaya diri, peduli, berani dan sopan